What is Agricultural Biotechnology Research Capacity in Developing Countries? - Falconi, César A. (International Service for National Agricultural Research, 1999)
In 1998 ISNAR has conducted a biotechnology research indicator survey in four national agricultural research systems in Mexico, Kenya, Indonesia and Zimbabwe, which provide overview information on the countries' agricultural biotechnology systems. Findings show that advanced biotechnology techniques are being used in only a few public-sector research organizations, and most organizations are still in the first stages of developing biotechnology research capacity. Although expenditures on agricultural biotechnology research grew annually in the countries, the proportion of biotechnology expenditures to total agricultural research expenditures was small, and the number of researchers grew much faster than expenditures. The public sector accounts for most of the total expenditures (92% on average in the four countries), and the participation of the private sector is limited. Most agricultural biotechnology research is focused on crops, with a limited scope for livestock. Agricultural biotechnology in the four countries has received particular attention from their governments. However, a comprehensive strategy is lacking for the development of biotechnology in the selected countries. An increase of investment levels in agricultural biotechnology research, the promotion of the private sector's involvement, the foster of public and private sector collaboration, the development of a comprehensive strategy are, among others, some of the policy recommendations proposed to overcome the identified limitations in the conduction of biotechnology research.